2020
DOI: 10.1111/cei.13413
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical and potential functional characteristics of different immune cells expressing CD28H/B7-H5 and their relationship with cancer prognosis

Abstract: Summary CD28H and B7‐H5 have been identified as receptor–ligand pairs in the B7/CD28 family, and have co‐stimulatory activity in immune cells. Here, we have systematically reviewed the research reports concerning the CD28H/B7‐H5 pathway. It was found that CD28H is mainly expressed in T cells and natural killer (NK) cells with naive and poorly differentiated properties, and repeated antigen stimulation leads to permanent loss of CD28H. In tumors, CD28H is mainly expressed in tissue‐resident memory (TRM) lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Moreover, CD103 and E-cadherin interaction play a vital role in granule polarization and exocytosis, enhancing recruitment and retention of tumor-antigen-specific TILs in human NSCLC. In human NSCLC, CD28H is mainly expressed in T RM cells and is thus associated with improved tumor prognosis ( 86 ). However, other studies conversely demonstrated opposite results that B7-H5 (the ligand of CD28H) was expressed in more than 60% of cases of NSCLC and was associated with worse prognosis.…”
Section: Lung T Rm Cells In Anti-tumor Immunitymentioning
confidence: 99%
“…Moreover, CD103 and E-cadherin interaction play a vital role in granule polarization and exocytosis, enhancing recruitment and retention of tumor-antigen-specific TILs in human NSCLC. In human NSCLC, CD28H is mainly expressed in T RM cells and is thus associated with improved tumor prognosis ( 86 ). However, other studies conversely demonstrated opposite results that B7-H5 (the ligand of CD28H) was expressed in more than 60% of cases of NSCLC and was associated with worse prognosis.…”
Section: Lung T Rm Cells In Anti-tumor Immunitymentioning
confidence: 99%
“…[ 14 ] In addition, HHLA2 is an inducer of the inflammatory response of antigen-presenting cells. [ 15 ] HHLA2 is widely expressed in a large proportion of tumor specimens, such as lung cancer, breast cancer, thyroid cancer, ovarian cancer, liver cancer, esophagus cancer, pancreatic cancer, bladder cancer, renal carcinoma, prostate cancer, and colon cancer. [ 16 ] Furthermore, recent studies have revealed that high HHLA2 protein expression in primary tumor tissues is associated with poor prognosis of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since there are few studies about sB7-H5 in AP, the mechanisms of sB7-H5 in AP are still unclear. According to the role of sB7-H5 in various cancers, it may have both coinhibitory functions in inhibiting the proliferation of human CD4 and CD8 T cells and the production of T cell cytokines or costimulatory functions in immune signalling [26]. In our study, the positive relationship between sB7-H5 and cytokines suggested a costimulatory function of sB7-H5 contributing to the progress of inflammation and severity in AP.…”
Section: Discussionmentioning
confidence: 48%